2014
DOI: 10.1016/j.jns.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of temporal lobe epilepsy by multimodal multinomial hippocampal response-driven models

Abstract: Purpose Multiple modalities are used in determining laterality in mesial temporal lobe epilepsy (mTLE). It is unclear how much different imaging modalities should be weighted in decision-making. The purpose of this study is to develop response-driven multimodal multinomial models for lateralization of epileptogenicity in mTLE patients based upon imaging features in order to maximize the accuracy of noninvasive studies. Methods and Materials The volumes, means and standard deviations of FLAIR intensity and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The quantitative ICC in reliability testing [56,58,65,66] and uncertainty analysis by Bayesian inference based on the posterior probability distribution [20,[67][68][69] are used for precise interpretation of MRI data and prediction of dynamic structural/functional model analysis. In the present study, the variance among healthy subjects, i.e., within-subject variability and the between-subject variability, had been assessed by the reliability testing through estimation of the ICC with 95 % confidence intervals using one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative ICC in reliability testing [56,58,65,66] and uncertainty analysis by Bayesian inference based on the posterior probability distribution [20,[67][68][69] are used for precise interpretation of MRI data and prediction of dynamic structural/functional model analysis. In the present study, the variance among healthy subjects, i.e., within-subject variability and the between-subject variability, had been assessed by the reliability testing through estimation of the ICC with 95 % confidence intervals using one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…The ample evidences of advanced research using multimodal combinational non-invasive neuroimaging techniques like MRI, MRS, f-MRI, FDG-PET, SPECT, and MEG have revealed that most of the cases of TLE patients are accompanied by pathological changes in brain structure and function network, including cortical and subcortical (hippocampus and parahippocampus) structures [12][13][14]. Such multimodal combinational imaging (structural and functional) approaches are being suggested to detect the laterization of TLE with ictal and interictal onset in pre-surgical diagnostic purpose [15][16][17][18][19][20]. Regardless, epilepsy occasionally is a clinical problem as regards medical management and the problem becomes acute in developing countries as there is often delay in clinical diagnosis due to the limited resources, large patient load, and health care manpower constraints [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For both coherence and nodal degree, statistically significant laterality measures between the left and right mTLE cohorts were considered as multivariate independent variables and incorporated into the development of response-driven models of laterality using logistic function regression (Hosmer Jr et al, 2013, Nazem-Zadeh et al, 2014a, Nazem-Zadeh et al, 2014b). …”
Section: Methodsmentioning
confidence: 99%
“…In order to assess how the multinomial logistic function generalized to an independent dataset and how accurately this response model performed in practice, a cross-validation was performed using the ‘leave-one-out’ approach [16]. The probability of detection on the test data was then calculated [17, 18]. …”
Section: Methodsmentioning
confidence: 99%